Antitumor activity of new chemical compounds in triple negative mammary adenocarcinoma models - María V Giolito; Cristian M Camacho; Maitena Martinez-Amezaga; Carla I Traficante; Rocío A Giordano; Patricia G Cornier; Ernesto G Mata; Carina ML Delpiccolo; Dora B Boggián; Antonela Del Giúdice; Leandro E Mainetti; Olga G Scharovsky; et al. (Future Science OA, 2020)
Aim: According to the need for the development of new anticancer agents, we have synthetized novel bioactive compounds and aimed to determine their antitumor action. Materials & methods: We describe in vitro studies evaluating the effect of 35 novel chemical compounds on two triple negative murine mammary adenocarcinoma tumors. Results & conclusion: Three compounds were selected because of their high antitumor activity and their low toxicity to normal cells. Their effect on tumor cells apoptosis, clonogenicity and migratory capacity, were determined. We found that the selected compounds showed inhibition of viability and clonogenic capacity, and promotion of apoptosis. They also decreased the migratory capacity of tumor cells. The results obtained suggest the likelihood of their future use as antitumor and/or antimetastatic agents.